Collaborative Governance Dalam Penanggulangan HIV/AIDS di Kota Pekanbaru - Susilawati Susilawati; Adianto Adianto (Pusat Riset dan Inovasi Nasional, 2024)
HIV/AIDS is an infectious disease which is a sensitive health issue to be discussed. HIV/AIDS can also cause loss of the immune system in humans. Pekanbaru City is the area with the most cases of HIV/AIDS in Riau Province. The purpose of this study was to find out collaborative governance in preventing HIV/AIDS in Pekanbaru City and to identify the inhibiting factors in preventing HIV/AIDS in Pekanbaru City. This study uses Purwanti's theory in Aziz Arrasyid (2021) which uses 3 indicators, namely: principled engagement, shared motivation and capacity for joint action. This study uses qualitative research with a case study approach. The informants of this study, namely the Pekanbaru City AIDS Commission (KPA), the Pekanbaru City Health Office and other related institutions conducted interviews, observations and documentation so that the required data were obtained such as primary data and secondary data and then analyzed so that conclusions could be drawn from the existing problems. The results of this study can be said to be not optimal, because there are still inhibiting factors in its implementation, namely the low participation of the community, especially the suspect community who are reluctant to admit to avoid discrimination from the surrounding community and the limited infrastructure provided.